SISTEM PENGINTEGRASIAN DATA PADA ORGANISASI KEAGAMAAN - Aristiawati Aristiawati (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Applications are made in the form of data integration program to be able to link the data on the server and client computers as well as making information systems program XYZ Center to generate the appropriate output as well as additional data usage for each program section. Integration in the form of data delivery from the server to the client computer and otherwise by using methods that convert between XML data with other data. Results of the experiment showed that the data on the server computer can be sent to the client computer as well as its reverse. As well as the program that is used to store database entered and issued the results desired by the user.